1990
DOI: 10.1002/neu.480210411
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic activation of the lobster cardiac ganglion

Abstract: The frequency of rhythmic burst activity of the isolated lobster cardiac ganglion is increased by exogenously applied acetylcholine and muscarinic agonists. Responses of individual motor neurons isolated from the ganglion by transection consist of a slow depolarization and repetitive bursting. The pharmacological profile of the receptors mediating this response is similar to that of vertebrate neuronal muscarinic receptors. Isolated ganglia incubated in the presence of [3H]-choline (18-19 h) exhibited radiolab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…In contrast, there is good evidence for the presence of amines and acetylcholine within the ganglion. For example, acetylcholine (Sullivan and Miller, 1990;Freschi and Livengood, 1989), gamma-amino-butyric acid (GABA) (Delgado et al, 2000) and dopamine (Fort et al, 2004), all of which modulate the activity of the heart, have been found within the ganglion. Both GABA and dopamine, although delivered locally, are nonetheless extrinsic modulators, since they derive from other sites in the nervous system.…”
Section: Cldh Is a Powerful Cardioactive Peptide In H Americanusmentioning
confidence: 99%
“…In contrast, there is good evidence for the presence of amines and acetylcholine within the ganglion. For example, acetylcholine (Sullivan and Miller, 1990;Freschi and Livengood, 1989), gamma-amino-butyric acid (GABA) (Delgado et al, 2000) and dopamine (Fort et al, 2004), all of which modulate the activity of the heart, have been found within the ganglion. Both GABA and dopamine, although delivered locally, are nonetheless extrinsic modulators, since they derive from other sites in the nervous system.…”
Section: Cldh Is a Powerful Cardioactive Peptide In H Americanusmentioning
confidence: 99%
“…Actions of cholinergic agonists and GABA on the cardiac ganglion Acetylcholine (ACh) is thought to be the neurotransmitter that is released from one of the acceleratory fibers projecting from the CNS to the CG to increase cardiac activity (Cooke, 2002), and the sensitivity of the CG to ACh and muscarinic cholinergic agonists has been described in other species (Freschi, 1991;Freschi and Livengood, 1989;Sullivan and Miller, 1990). Fig.·7A shows extracellular recordings in control (top trace) and in the presence of 10 -5 ·mol·l -1 pilocarpine, the muscarinic ACh receptor agonist (bottom trace).…”
Section: Effects Of Amines On the Cardiac Ganglionmentioning
confidence: 99%
“…It is known that the CG is modulated by substances released locally from regulatory nerve fibers and by hormones released from endocrine sites such as the pericardial organs (POs) (Alexandrowicz and Carlisle, 1953;Christie et al, 1995;Cooke, 2002;Cooke and Hartline, 1975;Li et al, 2003;Li et al, 2002;Pulver and Marder, 2002;Skiebe, 2001). The isolated CG is sensitive to biogenic amines (Benson, 1984;Berlind, 2001;Cooke and Hartline, 1975;Fort et al, 2004;Hashemzadeh-Gargari and Freschi, 1992b;Miller et al, 1984;Saver et al, 1999), GABA (Kerrison and Freschi, 1992), glutamate (Hashemzadeh-Gargari and Freschi, 1992a), cholinergic agonists (Freschi, 1991;Freschi and Livengood, 1989;Sullivan and Miller, 1990), proctolin (Freschi, 1989;Miller and Sullivan, 1981;Saver et al, 1999;Sullivan and Miller, 1984), crustacean cardioactive peptide (CCAP) (Saver et al, 1999), FMRFamide-like peptides (FLPs) (CruzBermúdez et al, 2006;Saver et al, 1999) and nitric oxide (Mahadevan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The transcript for this peptide hormone, which strongly activates cardiac activity, is present within the motor neurons of the CG. It has also been suggested that acetylcholine may act as an intrinsic modulator (reviewed in Cooke, 2002), since the ganglion can synthesize this transmitter (Sullivan and Miller, 1990) and is sensitive to it (Freschi and Livengood, 1989). In addition, the CG is thought to receive sensory feedback from the heart musculature through stretch-sensitive dendrites on the neurons of the ganglion itself (Cooke, 2002).…”
Section: Introductionmentioning
confidence: 99%